Studies On The Morphology Of Thelohanellus Sp., And The Effects Of Water Quality And Rainfall On Its Prevalence In Puntius Gonionotus (Bleeker) - Abdullah, Siti Zahrah (1994)

(untitled)
A myxosporean parasite belonging to the genus Thelohanellus, Kudo 1933 found infecting the gills of lampam jawa Puntius gonionotus (Bleeker), was studied. The morphological features of this myxosporean cysts and spores were examined through light and electron microscope to identify the species of Thelohanellus and the results were compared with other known Thelohanellus species. Morphologically, the spore size is 25.8 pm X 10.5 pm X 9.0 pm. These spores were tear-shaped or pyriform, having a distinct straight suture. Both membranous and mucous envelopes were distinctly conspicous; polar capsule size ranged from 1 1 - 1 7 pm (length) X 6-8 pm (width). Within the polar capsule were 8 - 12 coils of polar filament.